Faktor – Faktor yang Mempengaruhi Perilaku Kerja Gen Z Terhadap Kinerja Karyawan - Herliani Herliani; Yuddy Giovanna Priscilla (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – The high turnover among Gen-Z and millennials is influenced by a lack of work motivation, job dissatisfaction, an inharmonious work environment, and ineffective leadership. As a result, Gen-Z work behavior becomes inconsistent, which can have a negative influence on company performance. Therefore, it is important to emphasize job satisfaction and effective leadership to increase employee retention. So, employees can form positive and consistent work behaviors so that employees can effectively increase work productivity to achieve overall organizational success. Aim – This research seeks to explore how Work Motivation, Job Satisfaction, Leadership, and Work Environment affect the performance of Gen-Z employees. It specifically examines the role of Work Behavior as a mediator that links these factors to Employee Performance. Design/Methodology/Approach – This study uses a quantitative approach with purposive sampling. Data were collected via a Google Forms questionnaire and analyzed using SPSS and SmartPLS statistics.. Results and Discussion – The results of the study show that Work Motivation, Job Satisfaction, and Leadership significantly affect Employee Performance, both directly and through Work Behavior. In contrast, the Work Environment is insignificant, highlighting Gen Z's preference for intrinsic values and leadership over physical elements. Work Behavior mediates the relationship between Job Satisfaction and Leadership and performance, but not for Work Motivation and Work Environment. This research emphasizes the importance of job satisfaction, effective leadership, and value-based motivation to encourage positive work behaviors and increase productivity. Research Implications – This research highlights the importance of job satisfaction, transformational leadership, and value-based motivation to improve Gen Z's work behavior and performance. Limitations – The limitations of this study include a limited of respondents, namely employees in the electronics manufacturing sector in Batam City. In addition, the measurement of work behavior variables is only carried out in certain aspects.